2022
DOI: 10.1002/admt.202101704
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Capacitive Sensor Composed of Nanostructured Electrodes for Human–Machine Interface

Abstract: because the sensing information contains human behavior-related inputs to enable efficient communication, process control, and safety assurance. The technologies for behavior monitoring include cameras, [3] radar, [4] electromagnetic, [5] and capacitive sensing. Among the methods, capacitance sensing is unique in that both proximity and physical contact can be detected at a fraction of cost and power.Traditional capacitive sensors have been limited in flexibility, sensitivity, and proximity to serve HMI applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…The high aspect ratio structure and large surface area enhanced the fringing electric field, thus, the capacitive sensitivity. The CPC electrodes were fabricated using tensional fracture [38] and characterized in sample variability such as fabrication methods and sensing areas in our previous studies [39]. Therefore, in this paper, the fractured CPC was used as the single electrode to conduct all the expriments.…”
Section: Capacitive Liquid-level Measurement Using a Single Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…The high aspect ratio structure and large surface area enhanced the fringing electric field, thus, the capacitive sensitivity. The CPC electrodes were fabricated using tensional fracture [38] and characterized in sample variability such as fabrication methods and sensing areas in our previous studies [39]. Therefore, in this paper, the fractured CPC was used as the single electrode to conduct all the expriments.…”
Section: Capacitive Liquid-level Measurement Using a Single Electrodementioning
confidence: 99%
“…A single-electrode capacitive sensor was made of CPC as reported in previous research [38,39]. In short, the sensor was fabricated by trimming the CPC material into a 10 × 5 mm 2 rectangle.…”
Section: Fabrication Of a Single-ended Sensormentioning
confidence: 99%
“…The human can be seen as a conductor connecting to the ground, and when part of the human body, such as a finger, approximates the anode of a capacitive sensor, an equivalent capacitance is formed between the human body and the anode that is in parallel with the anode and cathode of the capacitive sensor, resulting in the increase of the total capacitance [ 51 ]. Based on that mechanism, capacitive sensors for contact and non-contact tactile sensing were proposed by Li et al [ 52 ], and a smart pad for proximity recognition was demonstrated.…”
Section: Tactile and Force Sensors For Hmimentioning
confidence: 99%
“…Moreover, different tactile sensing mechanisms can be combined for multifunctional tactile sensing, e.g., a heterogeneous tactile sensor able to sense stretching, bending, and compression individually was proposed by combining optical, microfluidic, and piezoresistive sensing mechanisms [ 74 ]. In addition to touch tactile interaction, proximity interaction is regarded as a generalized form of tactile, and sensing mechanisms, including capacitive [ 52 ], nearby charge induction [ 75 ], optical fiber [ 71 ], and magnetic field sensing [ 73 ], are utilized to realize non-contact tactile HMIs. Typical tactile and force sensors for human–machine interaction developed recently are summarized in Table 1 .…”
Section: Tactile and Force Sensors For Hmimentioning
confidence: 99%
“…[22][23][24] By presenting the sensor information to users in a simple and user-friendly interface, the HMI system enables a good user experience. [25,26] In particular, in the context of the coronavirus disease 2019 (COVID-19) pandemic, the use of smart electronic technology to achieve real-time and wireless interactive sensing is necessary. [27][28][29] Smart contact lenses (SCLs) have been employed for monitoring information regarding the eyes, including physical information (e.g., pressure and temperature) and chemical information (e.g., glucose, protein, and pH).…”
mentioning
confidence: 99%